Przecięcia biografii. Muzyczne spotkania Schulza - Skrzypczyk, Aleksandra (Zagadnienia Rodzajów Literackich, 2021)
The article is devoted to Bruno Schulz’s meetings with musicians. It shows not only a partial biography of the author of The Cinnamon Shops, filtered by these encounters, but also smaller fragments of lives of his friends. These intersected biographies create a story about inter-war contacts and relationships, which resulted in numerous epistolography and post-war memories that focused on Schulz’s life and oeuvre. The author of this text talks about the influence that these contacts might have had on Schulz’s perception of music and musicians. Furthermore, it shows how he translated these experiences into his prose. In the archive of Schulz’s life and work we can find traces of meetings with several music artists. There are also some traces of these meetings in the descriptions of organ grinders at Sanatorium Under The Sign of The Hourglass, Jewish musicians who we will find concerts in the story Spring, as well as in the descriptions of park and cafe musicians, mentioned in both series of stories. However, knowledge of these relationships survived primarily due to the letters. It should be noted that the preserved materials from his meetings with musicians have never been the subject of schulzology research in its entirety. Musicians inspired a few fragments of Schulz’s short stories. Artists whom he met at the beginning of the 20th century were not only performers of pre-war Poland, in particular his hometown of Drohobych, and Lviv, Warsaw, but also of Vienna and Paris. These friendships were important for his musical education, they shaped his thinking about music and his image of musicians. They must have had an impact on the descriptions of sounds in the world depicted in The Cinnamon Shops and his other stories, and finally — after the Holocaust — they let the legacy of Bruno Schulz be saved.